The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1159/000129419
|View full text |Cite
|
Sign up to set email alerts
|

Does Fibrin Glue Improve Drainage after Axillary Lymph Node Dissection? Prospective and Randomized Study in Humans

Abstract: The aim of this prospective and randomized study was to establish whether the use of fibrin glue was beneficial after axillary lymph node dissection. From January 1990 to January 1991, 40 women were randomized before surgery for breast cancer: 20 patients (group A) underwent vaporization of fibrin glue (Tissucol®, 5 ml of 500 IU thrombin) only in the area of axillary dissection; another 20 patients (group B) served as controls. The two groups were compared for age, number of nodes removed and involved, volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 14 publications
0
30
0
2
Order By: Relevance
“…Bovine thrombin has also proved unsuccessful in this regard. The employment of fibrin glue was encouraged after studies on animals [23,24], especially rats that underwent mastectomy, but in human studies no significant advantage was seen [25][26][27]. In a recent work, Johnson and Coll showed a lower rate of seroma formation using fibrin glue alone (36.8%) versus conventional drain placement (45%), but this difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine thrombin has also proved unsuccessful in this regard. The employment of fibrin glue was encouraged after studies on animals [23,24], especially rats that underwent mastectomy, but in human studies no significant advantage was seen [25][26][27]. In a recent work, Johnson and Coll showed a lower rate of seroma formation using fibrin glue alone (36.8%) versus conventional drain placement (45%), but this difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach can be to glue together the wound surfaces after dissection, and the introduction of fibrin glue 15 years ago suggested new possibilities [9]. Nevertheless, no advantage could be shown in the use of fibrin glue after lymphadenectomy [10,11]. Some studies reported a success in rat mastectomy models [12,13], but only two human reports [4,14] were able to reduce the incidence of seroma or daily drainage volume with fibrin glue after mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…18, 30 Vaxman et al reported that with the use the fibrin glue the total drain output increased. 31 Moreover, Dinsmore et al stated that not only the drainage volume increased but also the overall complication rate increased. 32 Dinsmore et al in spite of his criticism to fibrin glue usage, he put a hypothesis suggesting that the lack of benefit was due to the presence of drains that may interfere with the stabilization of a fibrin clot and with closure of the lymphatic capillaries.…”
Section: The Statistical Analysis Of Received Pre-and Postoperative Dmentioning
confidence: 99%